Effects of Employee Commitment, Organizational Culture, Personality and Employee Loyalty in Efforts to Change the Mental Management of Field Workers at ADIRA Finance Bandung Employees. - Rachmawati, Mariana; Sukandi, Pipin; Sofyandi, Herman; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The results to obtain results of the study (1) Commitment, Organizational Culture, Personality, Loyalty mentality, and Change Management have assessed both the Worker Field Finance PT ADIRA Bandung. (2) Obtaining Commitment study results have a positive relationship with the Cultural Organization of Field Workers at PT ADIRA Finance Bandung. (3) Obtain the results of the study of Commitment, Organizational Culture and Personality, partially and simultaneously influencing loyalty to PT ADIRA Finance Bandung. (4) Obtain the results of the study of Commitment, Organizational Culture and Personality, an effect partially or simultaneously to changes in the Field Worker Mental Manejeman PT ADIRA Finance Bandung. (5) Obtaining the results of the study of loyalty effect on Mental management changes in PT ADIRA Finance Bandung. Riset design While research causal (causal research) is to demonstrate a causal link one variable to another variable. Given the research that is exploratory, descriptive, and verification dangerous through better data collection of primary data and secondary data, this study Given the observation unit is working PT ADIRA Finance Bandung in determining sample study conducted by probability sampling techniques., This study will use a method of Structural Equation Modeling Based on this amount, the dissemination or distribution of the sample was divided evenly on each. Employee Commitment study Results: ADIRA Finance Branch Bandung declared Good Cultural Organization in the work environment in ADIRA Finance Cab, Bandung Good, Personality Lapanagn Workers still need to be improved as self-excellence employees; this happens when field workers do not focus on work and are not creative. Loyalty Finance ADIRA field workers Cab, Bandung Loyalty good, Change Management Finance ADIRA Field Worker Mental Cab, Bandung Good, Commitment Employee Relations, Organizational Culture, and Personality against ADIRA Finance Employee Loyalty Cab, Bandung expressed strong commitment; Organizational culture and personality affect loyalty. Commitment and organizational culture have no partial effect on Mental management changes. While personality affects the mental management changes. Loyalty effect on Mental manjemen changes.